Defying syntactic preservation in Alzheimer's disease: what type of impairment predicts syntactic change in dementia (if it does) and why? - Ivanova, Olga; Martínez-Nicolás, Israel; García-Piñuela, Elena; Meilán, Juan José G. (Frontiers in Language Sciences, 2023)
Many studies on syntax in dementia suggest that, despite syntactic simplification, speakers with Alzheimer’s disease (AD) retain the basic grammatical ability, being mainly affected in their comprehension and production of complex syntax. Moreover, there is no single position on the origin of syntactic decline in AD, which, according to some authors, can be linked to lexical-semantic deficit, or, according to others, to either cognitive or autonomous dysfunction. Shedding light on this question, however, may be particularly relevant for the early stages of AD, as it would help to improve the detection of cognitive impairment. The theoretical implications are no less important, for offering a view on the relationships between language levels themselves, and the cognitive impairment in dementia. To address both, in this study, we apply the model of syntactic maturity to the analysis of oral speech production elicited by the Cookie-theft description task. We assess a sample of 60 older adults (21 HC, 19 MCI, and 20 AD) through three indexes of syntactic maturity, measuring the proportion of sentences and clauses in discourse, their mean length, and the rate of their complexity. Our results show two important tendencies in AD: the preservation of general syntactic ability and the disturbance of the indexes of syntactic complexity.